Fat'hu al bariy sharh Sahih al Imam Abi Abdullah Muhammad Ibn Isma'il al Bukhari - Ahmad Ibn Ali Ibn-Hajjar-al-Asqalani (Maktabah al Salafiyyah)
ws.jl.,4-6,8-12.c.1-2,jl.2,7c.1-3 jl.11.c.1-4,/stoc3=36 eks